Sodium methyl carbonate as an effective C1 synthon. Synthesis of carboxylic acids, benzophenones, and unsymmetrical ketones - Hurst, Timothy E.; Deichert, Julie A.; Kapeniak, Lucas; Lee, Roland; Harris, Jesse; Jessop, Philip G.; Snieckus, Victor (My University, 2019)
Reported is the synthesis of carboxylic acids, symmetrical ketones, and unsymmetrical ketones with selectivity achieved by exploiting the differential reactivity of sodium methyl carbonate with Grignard and organolithium reagents.
Keywords: sodium methyl carbonate; synthesis of symmetrical ketones; unsymmetrical ketones; Grignard reagents; organolithium; C1 synthon; alkyl metal carbonates; carboxylic acids; benzophenones